Comparison of Large and Small Doses of Radioactive 131I in the Treatment of Patients with Cardiac Damage Associated with Thyrotoxicosis - Felt, V.; Váňa, S.; Němec, J.; Šilink, C. (Nuklearmedizin - NuclearMedicine, 1971)
A comparison of the effect of large and small doses of radioiodine in patients with cardiac thyrotoxicosis revealed that after large doses thyrotoxicosis recedes more rapidly but is associated with a high incidence of hypothyroidism in subsequent years. After small doses the incidence of hypothyroidism is smaller; there is, however, a high percentage of persisting thyrotoxicoses. The sensitivity to radioiodine is higher in diffuse goiter, in small goiters, and after thyroidectomy.Large and small doses have approximately the same effect on the regression of decompensation and the incidence of paroxysmal atrial fibrillation, provided that treatment is supplemented by thyrostatic, antiarrhythmic, cardiotonic, and diuretic drugs. Larger doses of radioiodine had a more favourable effect on the reversion to sinus rhythm in patients with permanent atrial fibrillation.